A Rare Case of Rectus Muscle Twitching Due to Abandoned Uncapped Pacemaker Leads - Al-Khdour, Issa; AlAqra, Amro; Nairat, Moath; Marai, Ibrahim; Yaghi, Nadine; Awwad, Fateh (Curēus (Palo Alto, CA), 2023)
Extra-cardiac stimulation after cardiac pacemaker implantation is seldom seen in the cardiac field. However, this case report demonstrates an unusual symptom of persistent abdominal twitching in a 42-year-old male patient who underwent pacemaker replacement, lasting for 15 years. Initially, it was attributed to diaphragmatic pacing by the new pacemaker. Despite several attempts to replace the endocardial leads, the patient's symptoms did not improve. Finally, he was referred to our hospital, where our team conducted further investigations and discovered that the old pacemaker lead was exposed, leading to excitation of the rectus muscle.